Factor Influencing Intention to Adopt Fintech in Pakistan: A Mediating Effect of Customer Attitude - Khan, Ahmad Talha; Kamran, Rizwan; Rehan, Muhammad Farooq; Allahrakha, Rubina (Pakistan Journal of Humanities and Social Sciences, 2023)
This study's goal is to better understand the variables that affect Pakistani consumers' acceptance of and use of Financial Technology (FinTech) services in the banking industry. Data from a sample size of 339 banking clients were gathered using a research methodology based on quantitative approaches and a causal approach. According to the study's findings, people's intentions to utilise financial technology (FinTech) are greatly impacted by how beneficial they believe the technology to be and how secure they believe it to be. The relationship between perceived usability, perceived usability, and intention to utilise financial technology is mediated by client attitudes. Additionally, a key factor in affecting the adoption of financial technology is the perspectives of the customers. This demonstrates the need to enhance user experience and effectively address worries about the degree of security. With the aim of encouraging the uptake of FinTech services and fostering a financially stable environment, policymakers, financial institutions, and FinTech businesses in Pakistan may make use of these findings. This research significantly adds to the body of knowledge on technology adoption and provides a strong foundation for further research in the dynamic and ever-evolving field of financial technology (FinTech). This research also lays a strong platform for future studies in the area of information technology (IT).